Two-photon fluorescence lifetime imaging monitors metabolic changes during wound healing of corneal epithelial cells in vitro - Gehlsen, Uta; Oetke, Andrea; Szaszak, Marta; Koop, Norbert; Paulsen, Friedrich; Gebert, Andreas; Huettmann, Gereon; Steven, Philipp (Graefes Archive For Clinical and Experimental Ophthalmology, 2012)
Background Early and correct diagnosis of delayed or absent corneal epithelial wound healing is a key factor in the prevention of infection and consecutive destruction of the corneal stroma with impending irreversible visual loss. Two-photon microscopy (TPM) is a novel technology that has potential to depict epithelial cells and to evaluate cellular function by measuring autofluorescence properties such as fluorescence intensity and fluorescence lifetimes of metabolic co-factors such as NAD(P)H. Methods Using non-invasive TPM in a tissue-culture scratch model and an organ-culture erosion model, fluorescence intensity and fluorescence lifetimes of NAD(P)H were measured before and during closure of the epithelial wounds. Influence of temperature and selective inhibition of metabolism on intensity and lifetimes were tested additionally. Results Decrease of temperature resulted in significant increase of fluorescence lifetimes and decrease of the relative amount of free NAD(P)H due to decreased global metabolism. Increase in temperature and upregulation of glycolysis through blocking the mitochondrial electron transport chain by rotenone resulted in increased intensity, decreased lifetimes and increase in the relative amount of free NAD(P)H. Changes of lifetimes and free:protein-bound NAD(P)H ratios were similar to changes measured during wound healing in both scratch and erosion models. Conclusions Fluorescence lifetime measurements (FLIM) detected enhancement of cellular metabolism following epithelial damage in both models. The prospective detection of cellular autofluorescence in vivo, in particular FLIM of metabolic cofactor NAD(P)H, has the potential to become an indispensible tool in clinical use to differentiate healing from non-healing epithelial cells and to evaluate effects of newly developed substances on cellular metabolism in preclinical and clinical trials. © Springer-Verlag 2012.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Corneal epithelium; Metabolism; Two-photon microscopy; Wound healing